Control of stereoselectivity in 4-tert-butylphenol hydrogenation over a carbon-supported rhodium catalyst by carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Ebina, Takeo; Shirai, Masayuki (Chemistry Letters, 2006)
cis-4-tert-Butylcyclohexanol was obtained with a high cis ratio (cis/(cis + trans) = 0.9) in the hydrogenation of 4-tert-butylphenol over a carbon-supported rhodium catalyst along with hydrochloric acid in supercritical carbon dioxide solvent.

Conversion of benzyl phenyl ether to monoaromatics in high-temperature aqueous ethanol solution under high-pressure carbon dioxide conditions - Taniguchi, Kenkichi; Kusumawati, Etty N.; Nanao, Hidetaka; Rode, Chandrashekhar V.; Sato, Osamu; Yamaguchi, Aritomo; Shirai, Masayuki (New Journal of Chemistry, 2023)
Solvolysis of benzyl phenyl ether (BPE), which is a model compound of lignin ether linkage, was studied in an aqueous ethanol solution, which can be obtained from bioethanol, under high-pressure carbon dioxide conditions. A batch study revealed that BPE solvolysis to monoaromatics (benzyl ethyl ether (BEE), benzyl alcohol (BA), and phenol (Ph)) proceeded in aqueous ethanol solution over 523 K and the addition of high-pressure carbon dioxide enhanced the initial solvolysis rate and suppressed the side reaction (hydrogenolysis to toluene (TL)). The ethanol molar fraction (ethanol-water volume ratio) is the key factor for the solvolysis reaction, and the highest monoaromatic yield of 72.9% (BEE 10.7%, BA 19.3%, Ph 37.9%, and TL 5.1%) was obtained in aqueous ethanol solution (2 cm(3) : 1 cm(3) = water:ethanol) at 598 K for 3 h under a pressure of 18 MPa of carbon dioxide. The solvolysis reaction proceeded continuously to produce monoaromatics with a flow system. A monoaromatic yield of 76.7% (BEE 8.6%, BA 19.7%, Ph 39.6%, and TL 8.9%) was obtained, and the formation rates were 2.7 x 10(-4) mmol min(-1) for BEE, 6.2 x 10(-4) mmol min(-1) for BA, and 12.4 x 10(-4) mmol min(-1) for Ph at 598 K under flowing water (26 mmol min(-1)), ethanol solution (4.1 mmol min(-1)), carbon dioxide (1.2 mmol min(-1)), and BPE (15.6 x 10(-4) mmol min(-1)) under a total pressure of 40 MPa.